Effects of coumarin and its interaction with gibberellic acid on the germination of Prosopis juliflora (Sw) d.c. - Perez, Sonia Cristina J. G. de A.; Moraes, José Antônio P.V de (Pesquisa Agropecuaria Brasileira, 1991)
The aim of this work was to study the effects of coumarin and its interaction with gibberellic acid on the germination of Prosopis juliflora seeds. They were plunged in sulfuric acid during 30 seconds before being placed in a growth chamber (Fanem) at 35°C, (optimal temperature). Exogenous application of coumarin in concentration of 0,1; 0,2; 1,0; 2,0; 5,0 and 10,0 mM caused a delay and a reduction in the number of germinated seeds and in the speed of the process. At 10,0 mM germination was absent. Germination inhibition by coumarin till the concentration of 5,0 mM was partially reduced by gibberellic acid at 10-5M. By the other side, at 10,0 mM, the inhibitory effect of coumarin was not alleviated when gibberellic acid (1,0-5 M) or gibberellic acid (1,5 mM) plus kinetin (1,0 mM) was added in the germination media.